2008
DOI: 10.1111/j.1537-2995.2008.01932.x
|View full text |Cite
|
Sign up to set email alerts
|

Validation of an automated immunoglobulin G–only cytomegalovirus (CMV) antibody screening assay and an assessment of the risk of transfusion transmitted CMV from seronegative blood

Abstract: BACKGROUND:Cytomegalovirus (CMV) antibody donor screening assays have predominantly included both immunoglobulin G (IgG) and immunoglobulin M (IgM) detection. However, since in the majority of cases both CMV IgG and IgM are detected concomitantly during early seroconversion, CMV assays based only on IgG are now widely applied for donor screening. STUDY DESIGN AND METHODS:The performance of an automated microparticle CMV IgG assay (Abbott AxSYM CMV IgG microparticle enzyme immunoassay [MEIA]) was compared with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…Notwithstanding this, the estimates are well below the threshold of 1 in 1 million, generally considered negligible when contextualizing transfusion risks and substantially lower than our published estimate for the risk per non‐leucodepleted, sero‐negative unit of approximately 1 in 66 000 (range, 1 in 165 000–1 in 42 000) . Importantly though, the LD‐only and serological testing risk estimates cannot be compared because of the differing methods of derivation and cannot be deemed additive because there is likely significant overlap.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Notwithstanding this, the estimates are well below the threshold of 1 in 1 million, generally considered negligible when contextualizing transfusion risks and substantially lower than our published estimate for the risk per non‐leucodepleted, sero‐negative unit of approximately 1 in 66 000 (range, 1 in 165 000–1 in 42 000) . Importantly though, the LD‐only and serological testing risk estimates cannot be compared because of the differing methods of derivation and cannot be deemed additive because there is likely significant overlap.…”
Section: Discussionmentioning
confidence: 56%
“…Even with this substantial risk reduction, the limitations of both major strategies (sero‐negative or leucodepleted) result in reported breakthrough infections at a rate of 1–7% per transfused recipient . Modelling performed prior to the 2008 implementation of universal leucodepletion for platelets and red cell concentrates (red cells) in Australia estimated the residual risk per sero‐negative (non‐leucodepleted) unit was approximately 1 in 66 000 (range, 42 000–165 000) . Interestingly, this modelled estimate is substantially lower than the rate of up to 0·23% (1 in 2300) per unit reported for non‐CMV antibody screened, leucodepleted cellular products in prospective clinical follow‐up of transfusion recipients in the USA .…”
Section: Introductionmentioning
confidence: 99%
“…The same authors showed that CMV DNA levels peak during the late phase of primary infection in newly seropositive donors. 8 Although whether a rationale exists for introducing screening for specific IgM in addition to IgG remains to be determined, 18 the chemiluminescence tests for CMV currently applied by the Japanese Red Cross detect only IgG. Although we have discussed seroprevalence and its relationship with the presence of DNA by interpreting IgM positivity as representing primary infection, reactivity for CMV-specific IgM measured by EIAs must be considered with caution.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to transplant, CMV serology should be performed on all donors and recipients. Tests for anti-CMV IgG are recommended, as they have better specificity than IgM or combination IgG and IgM tests, neither of which should be used for pretransplant screening, as false positive tests for IgM may significantly decrease test specificity (54)(55)(56). If the initial result was negative and there was a significant lapse in time after testing, serology should be repeated at the time of SOT, in order to not overlook those donors or recipients who are now seropositive.…”
Section: Diagnosismentioning
confidence: 99%